Two Tier Hox Collinearity Mediates Vertebrate Axial Patterning - Durston, Antony J. (Frontiers in Cell and Developmental Biology, 2018)
A two tier mechanism mediates Hox collinearity. Besides the familiar collinear chromatin modification within each Hox cluster (nanocollinearity), there is also a macrocollinearity tier. Individual Hox clusters and individual cells are coordinated and synchronised to generate multiscale (macro and nano) collinearity in the early vertebrate embryo. Macro-collinearity is mediated by three non cell autonomous Hox-Hox interactions. These mediate temporal collinearity in early NOM (non organiser mesoderm), time space translation (TST) where temporal collinearity is translated to spatial collinearity along the early embryo’s main body axis and neural transformation, where Hox expression is copied monospecifically from NOM mesoderm to overlying neurectoderm (NE) in the late gastrula. Unlike nanocollinearity, which is Hox cluster restricted, axial macrocollinearity extends into the head and EAD domains, thus covering the whole embryonic anterior-posterior (A-P) axis. The whole TST mechanism interacts with A-P signalling pathways via ‘decision points’, separating different domains on the axis.